PELAKSANAAN PEMBERIAN IZIN LINGKUNGAN BERDASARKAN PERATURAN PEMERINTAH NOMOR 27 TAHUN 2012 OLEH BADAN LINGKUNGAN HIDUP DI KOTA PEKANBARU TAHUN 2016 - Yofi Yoanda; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study would like to know and analyze the implementation of Environmental Permit Based on Government Regulation No. 27 of 2012 by the Environment Agency in Pekanbaru City in 2016. describe the variables that may affect the Implementation of Environmental License, obstacles to the efforts that need to be done in the implementation of licensing Environment in Pekanbaru City.This research uses qualitative research method by entering descriptive data assessment. Taking informant in this research is Purposive Sampling that is technique of taking data source with certain consideration, certain consideration of this person who is considered most know about what we expect or as ruler so that will facilitate the researcher to explore object / social situation under study.From the result of the research, it can be concluded that the implementation of environmental permit in Pekanbaru City has not fully fulfilled the provisions as regulated in Government Regulation No. 27 of 2012 on Environmental Permit, such as the implementation of environmental management and monitoring does not involve the community. The inhibiting factor in the implementation of environmental permit in Pekanbaru City is the limited human resources capable of assessing a business plan and / or activity, business actors still consider the environmental permit incriminating in terms of cost. Supervision by related agencies in the environmental field in Pekanbaru City hit the cost problem. Efforts that need to be done in the framework of the implementation of environmental permit in Pekanbaru City is to improve the human resources capable of assessing a business plan and / or activity, streamlining the involvement of the community, supervision is required by way of sudden inspection.Keywords: Implementation, Environmental Permit.